Deliberative Democracy and Precautionary Public Reasoning: Exploratory Thoughts - Johnson, Genevieve (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2006)
Because public policy is legally binding and, perhaps more pointedly, can have pervasive social and environmental consequences for the autonomy of persons, it should be justifiable to those it could so affect. What is much more controversial, and what constitutes the basic intuitive claim of this exploratory paper, is that certain public policies should be morally justifiable to both existing and future persons. My concern is with policies in such areas as energy, climate change control, nuclear waste management, natural resources management, and genomics research and commercialization, which can no doubt improve our lives and our descendant’s lives, but which can also result in tremendous adverse effects for centuries to come. In this short paper, I suggest that the ideal of deliberative democracy provides a way of morally justifying such policies to both existing and future generations. If we take seriously the requirements of this ideal, we may have to modify our public reasoning so that it includes reasons that are generally acceptable among contemporaries as well as reasons that would be acceptable to posterity. The suggestion I make in this paper is that integral to the ideal of deliberative democracy in the transgenerational context is a future-oriented and precautionary public reasoning.